Cruise passengers' risk reduction strategies in the wake of COVID-19. Issue 11 (2nd November 2021) - Holland, Jennifer; Mazzarol, Tim; Soutar, Geoffrey N.; Tapsall, Suellen; Elliott, Wendy A.
ABSTRACT: The COVID-19 pandemic devastated the cruise sector with an initial global shutdown and ongoing patchy resumption, widespread reporting of virus transmission onboard and billions of dollars in economic losses. This study explores how COVID-19 has impacted Australian and UK consumers' risk perceptions, revealing cruises are no longer considered "safe". Consumers are more negative about, and less willing to, cruise. Cluster and Leximancer analyses identified five distinct market segments differentiated by the extent of travel risk they perceived. Specific risk reduction strategies are identified and include risk mitigation, use of risk relievers, and risk avoidance.